GIF Art in the Metamodern Era (Cinéma & Cie. Film and Media Studies Journal, 2016)
This essay offers an exploration of the recent phenomenon of GIF art, in light of the cultural attitude that has come to be known under the term of ‘metamodernism’. Unlike other recent theories (New Realism, Hypermodernity, Altermodernism, and so on) that have tried to conceptualize the ‘cultural logic’ of the present age as a kind of neo-modernist dismissal of postmodernism, metamodernism is not intended to dispose of the notion of postmodernism all together. Instead, it is defined as ‘an oscillation between aspects of both modernism and postmodernism’ (Timotheus Vermeulen and Robin van den Akker). The article argues that GIF art can be held as a major contemporary expression of a truly metamodernist ‘structure of feeling’, following a refunctionalizing, in artistic terms, the Graphics Interchange Format. GIF art is today an extraordinarily vital, well-diffused and fragmented field of experimentation, where new uses of the moving image are continuously developed and tested. Its interest for film studies lies in the fact that it almost literally reinvents the cinematographic device (disposif) in a digital context, to the point that it has been termed ‘a form of minicinema entirely native to the Internet’ (Tom Moody).